THE SOLUTION OF THE THEORY OF JUSTICE AS EQUITY TO STABILIZE SOCIETY WITH THE INFLUENCE OF SOCIAL NETWORKS - Alonso, Nathália (REPAE - Revista de Ensino e Pesquisa em Administração e Engenharia, 2022)
This article makes, through exploratory research, an analysis of the interference of social networks in modern democracies, mainly taking into account the result of the last electoral elections in Brazil and the United States in the years 2018 and 2016. In addition to electoralelections , emphasizes the influence of social networks and fake news on life in society and on the relationship between people.Then, starting from the construction of the understanding that such influence would generate intense social disputes, it seeks to establish elements to understand whether the work "A Theory of Justice" with the theory of justice as equity formulated by John Rawls would find ways to reestablish consensus and public reason considering that kind of influence did not exist before.